Luteolin-rich fraction from Perilla frutescens seed meal inhibits spike glycoprotein S1 of SARS-CoV-2-induced NLRP3 inflammasome lung cell inflammation via regulation of JAK1/STAT3 pathway: A potential anti-inflammatory compound against inflammation-induced long-COVID - Dissook, Sivamoke; Umsumarng, Sonthaya; Mapoung, Sariya; Semmarath, Warathit; Arjsri, Punnida; Srisawad, Kamonwan; Dejkriengkraikul, Pornngarm (Frontiers in Medicine, 2023)
The multi-systemic inflammation as a result of COVID-19 can persevere long after the initial symptoms of the illness have subsided. These effects are referred to as Long-COVID. Our research focused on the contribution of the Spike protein S1 subunit of SARS-CoV-2 (Spike S1) on the lung inflammation mediated by NLRP3 inflammasome machinery and the cytokine releases, interleukin 6 (IL-6), IL-1beta, and IL-18, in lung epithelial cells. This study has attempted to identify the naturally- occurring agents that act against inflammation-related long-COVID. The seed meal of Perilla frutescens (P. frutescens), which contains two major dietary polyphenols (rosmarinic acid and luteolin), has been reported to exhibit anti-inflammation activities. Therefore, we have established the ethyl acetate fraction of P. frutescens seed meal (PFEA) and determined its anti-inflammatory effects on Spike S1 exposure in A549 lung cells. Rosmarinic acid (Ra) and luteolin (Lu) in PFEA were identified using the HPLC technique. PFEA was found to contain Ra (388.70±11.12 mg/g extract) and Lu (248.82±12.34 mg/g extract) as its major polyphenols. Accordingly, A549 lung cells were pre-treated with PFEA (12.5-100 μg/mL) and its two major compounds (2.5-20 μg/mL) prior to the Spike S1 exposure at 100 ng/mL. As determined by RT-PCR and ELISA, PFEA dose-dependently exhibited anti-inflammatory properties upon Spike S1-exposed A549 cells through IL-6, IL-1β, IL-18, and NLRP3 gene suppressions, as well as IL-6, IL-1β, and IL-18 cytokine releases with statistical significance (p<0.05). Importantly, Lu possesses superior anti-inflammatory properties when compared with Ra (p< 0.01). Subsequently, PFEA and Lu were investigated for their inhibitory mechanisms by western blot technique. PFEA and Lu effectively attenuated a Spike S1-induced inflammatory response through downregulation of the JAK1/STAT3-inflammasome-dependent inflammatory pathway as evidenced by the downregulation of NLRP3, ASC, and cleaved-caspase-1 of the NLRP3 inflammasome components and by modulating the phosphorylation of JAK1 and STAT3 proteins (p< 0.05). The findings suggested that luteolin and PFEA can modulate the signaling cascades that regulate Spike S1-induced lung inflammation during the incidence of Long-COVID. Consequently, luteolin and P. frutescens may be introduced as potential candidates in the preventive therapeutic strategy for inflammation-related post-acute sequelae of COVID-19.